The awareness and utilisation of tax investment incentives on environmental protection activities - Bin Deris M.S.; Binti Buniamin S.; Binti Ahmad N.; Bin Alrazi B. (2023)
This study investigates the awareness and utilisation of the Tax Investment Incentives (TII) under Income Tax Act 1967 (ITA) and the Promotion of Investment Acts 1986 (PIA) on Environmental Protection Activity (EPA). Additionally, the study examines the type of EPA undertaken by Malaysian Public Listed Companies. Data are obtained using self-administered questionnaires which were mailed directly to the respondents who were Chief Financial Officers, accountants, tax managers or Board of Directors. The study discovered that 17(27%) companies were involved in waste recycling; 15(24%) in storage, treatment and disposal of toxic and hazardous waste; and 11(18%) in waste water management. The descriptive analysis reveals that 48(77%) out of the 62 companies were aware of the availability of TII on EPA. Surprisingly, only four companies ever utilised the TII on EPA which includes Investment Tax Allowance, Accelerated Capital Allowance, Reinvestment Allowance and Double Deduction. The utilisations are based on their capital expenditure on plant and equipment, motor vehicle and industrial building. 2009 IEEE.